Job Insecurity - Kuvalekar, Aditya and Elliot, Lipnowski (American Economic Journal Microeconomics)
We examine the relationship between job security and productivity in a fixed wage worker-firm relationship facing match quality uncertainty. The worker's action affects both learning and current productivity. The firm, seeing worker behavior and outcomes, makes a firing decision. As bad news accrues, the firm cannot commit to retain the worker. This creates perverse incentives: the worker strategically slows learning, harming productivity. We fully characterize the unique equilibrium in our continuous-time game. Consistent with some evidence in organizational psychology, the relationship between job insecurity and productivity is U-shaped: a worker is least productive when his job is moderately secure. - Reproduced
Keywords: Human Capital; Skills; Occupational Choice; Labor Productivity